Degradabilidade ruminal do resíduo do guaraná: seu potencial para o uso e estudo na alimentação de ruminantes - Negreiros, Ronan de Souza (Brasil, 2022)
The cultivation of guarana is one of the agro-industrial activities that stands out and moves the country's economy. As it is a legitimately Brazilian plant, it has great economic and social importance, especially in the Amazon region, due to the high demand for almonds by the beverage industries to supply the large soft drinks and energy markets. Therefore, the objective of the present study was to evaluate the ruminal degradability of the guarana (Paullinia cupana) residue (integument and rest of almonds) and to perform the chemical composition and the possibility of using it in the ration of ruminant animals. The "in situ" degradability test was used in a rumen fistulated bovine with an average live weight of 450 kg fed (Hay grass piatã) twice a day at 8:00 am and 4:00 pm, supplemented with mineral salt ad libitum. and free for grazing. The incubation periods corresponded to the times of 0, 2, 4, 8, 12, 24, 48 and 72 hours. The guarana residue showed low DM and CP degradability, probably due to the tannin contents, however, it seems to have good characteristics for use in ruminant feed in amounts that do not negatively affect degradability. Further studies are suggested to recommend its safe use.